Evaluation of Consumer Behaviour & Assessment of Factors Determining Acceptance of Solar Energy Products - Kansal, Bindiya; Pathania, Ajay Kumar; Saini, Jagdish Raj (Indian Journal of Marketing, 2017)
Punjab is one of the largest energy consuming states in India, where people face the shortage of electricity. Punjab needs an alternative source of energy. However, still, the state has not adopted solar energy as an alternative source of energy. This paper attempted to assess the awareness level and identify the major barriers that limit the diffusion of solar energy products. An exploratory factor analysis was applied to discover the factors that determine acceptance of solar energy products. The survey was conducted in Punjab covering six cities. Descriptive analysis was done to evaluate the present status of solar energy awareness. The factor analysis revealed five factors that explained more than 60% of variance. Lack of financial support by government and high initial costs were identified as the major barriers that limit diffusion of solar energy products.